Improving the Quality of Public Services at the Nan Provincial Industrial Office by Applying the Principles of Sangha Vatthu Dhamma - Wongchai, Songyot; Khumpong, Worapat; (Plongkhun), PhrakruSutananthapandit Watcharapong (Journal of Thammawat, 2025)
The purpose of this article was: 1) to study the quality of public service of the Nan Provincial Industrial Office; 2) to study relationship between the principles of social welfare and quality of public service of the Nan Provincial Industrial Office; and 3) to present the development of quality of public service of the Nan Provincial Industrial Office by applying the principles of social welfare. This research was a mixed-methods study. The data were collected from a sample of 157 people by random sampling using Taro Yamane's formula. The descriptive data analysis was performed using frequency, percentage, mean, and standard deviation. The correlation analysis was performed using Pearson's correlation coefficient. In-depth interviews were conducted with 10 key informants. The data analysis was performed using the content summary technique to present the guidelines. The research revealed that: 1) the quality of public service of the Nan Provincial Industrial Office based on the principles of social welfare was at a high level overall. The public service of the Nan Provincial Industrial Office was at a high level overall. 2) The relationship between the principles of social welfare and the quality of public service of the Nan Provincial Industrial Office was at a very high level overall. (R=.832**) The positive relationship was statistically significant at a 0.01 level. And 3) the development of quality Providing services to the public by the Nan Provincial Industrial Office by applying the principles of social welfare found that the services should be attentive, provide advice and communicate with polite, gentle words, be clear and easily understood. Reduce steps and supporting documents for providing services, clearly show the steps, supporting documents, and guidelines for practice, access service recipients via electronic systems for convenience and speed, and increase operational skills for officials to have knowledge in providing services.